Photosynthetic traits of Phragmites australis along an ecological gradient and developmental stages - Tóth, Viktor R. (Frontiers in Plant Science, 2025)
Common reed (Phragmites australis) is a cosmopolitan species, though its dieback is a worldwide phenomenon. In order to assess the evolutionary role of phenotypic plasticity in a successful plant, the values and plasticity of photophysiological traits of Phragmites australis were investigated in the Lake Fertő wetlands at 5 sites with different degrees of reed degradation and along a seasonal sequence. On the one hand, along the established ecological degradation gradient, photophysiological traits of Phragmites changed significantly, affecting plant productivity, although no consistent gradient-type trends were observed. Gradual changes within a season in the values of photosynthetic traits were observed that were recorded in both degraded and stable stands, suggesting a universal response to seasonally changing environmental conditions that could not be overridden by the ecological gradient. On the other hand, reed plants exposed to different levels of degradation showed comparable physiological plasticity; there was no difference in trait variability between stable and degraded stands. This relatively uniform plasticity is likely to contribute to the resilience of reed plants by providing a wider range of adaptive traits under different conditions. In contrast, the 150-200% gradual change in photophysiological trait plasticity with senescence in Phragmites was also demonstrated, reflecting a more dynamic response of the photosynthetic apparatus to seasonal changes. Senescence affected the plasticity of plant traits independently of their degradation status, suggesting a more universal nature of seasonal changes. This research shows that under conditions of conservative resource use determined by stressful habitats, trait values respond to conditions, while trait plasticity shows minimal changes. Furthermore, phenological sequence significantly influenced both the values and the plasticity of the photosynthetic traits studied. Our results underline the impact of ecological degradation on reed physiology and highlight the importance of understanding both trait values and plasticity in plant responses to environmental and seasonal change.